The shadow economy and work in the shadow: What do we (not) know? - Friedrich Schneider (Institute for the Study of Labor (IZA), 2012)
In this paper the main focus lies on the shadow economy and on work in the shadow in OECD, developing and transition countries. Besides informal employment in the rural and non-rural sector also other measures of informal employment like the share of employees not covered by social security, own account workers or unpaid family workers are shown. The most influential factors on the shadow economy and/or shadow labor force are tax policies and state regulation, which, if they rise, increase both. Furthermore the discussion of the recent micro studies underline that economic opportunities, the overall burden of the state (taxes and regulations), the general situation on the labor market, and unemployment are crucial for an understanding of the dynamics of the shadow economy and especially the shadow labor force.
urn:nbn:de:101:1-201207125564
Keywords: K42; H26; D78; 330; shadow economy; undeclared work; shadow labor force; tax morale; tax pressure; state regulation; labor market; Schattenwirtschaft; Schwarzarbeit; Steuerbelastung; Regulierung; OECD-Staaten; Entwicklungsländer; Transformationsstaaten